Ideal world of Mrs. Widder's soirée musicale : Music and difference in nineteenth-century Ontario - Guiguet, Kristina Marie, 1953- (Book collections on Project MUSE., 2004)
"The printed program of Mrs. Widder's 1844 Soiree Musicale, a formal concert at her lavish Toronto home, lists eleven musicians performing opera, parlour ballads, and glees. This information helped trace the networks which drew a working tenor and leisured Lady and Gentlemen Amateurs into a brilliant program balancing aesthetics with social politics. The Widder program reveals how conventions linking class and gender with musical genre and local issues shaped the meaning of musical life both public and private. The Soiree Musicale, a concert form transplanted from imperial London, was the embodiment of an idealized hierarchical universe."--Jacket.